Porewater geochemistry of sediment core M167_33-1 (GeoB24225-1) - Christopher Schmidt; Hanna Zehnle; Walter Menapace (PANGAEA, 2021)
Pore water samples for cruise M167 were taken from gravity cores (GC) and 1 ROV Squid push cores. The sampling was done in the geology laboratory of the ship. Upon core retrieval, we took 2-3 cm wide sediment slices from the working halves of the GC. The spacing of the sampling was chosen according to core recovery, but did normally not exceed 20 cm for GCs. Push cores were sampled every 2 cm. Sediments both at the splitted surface and in contact with the liner were not sampled to avoid potential contamination with seawater. A GEOMAR argon-gas squeezer was used to extract porewater from the sediments. In addition to the squeezing method, some gravity cores were treated with rhizons (purchased from Rhizosphere, Netherlands) in order to gain pore fluids from undisturbed whole cores. Push core was sampled only with rhizons. Therefore, small holes were drilled in the plastic liner and rhizons were placed in the sediments. The rhizons were connected with 10 ml syringes. Syringes were draw up and hold at the position with a wooden spacer in order to keep the vacuum. Extracted pore fluids were transferred afterwards into 20 ml plastic vials. On board analyses include titration of Total Alkalinity. The remaining pore water was subsampled for further onshore analysis. The analyses with IC and ICP took place in the Geomar laboratories.